The privacy dilemma. Issue 2 (February 2015) - Mansfield-Devine, Steve
Abstract : We often encounter the law of unintended consequences in the information security world. For example, tools intended to allow security professionals to test, stress or explore networks and servers in order to improve security are also frequently exploited by malicious hackers intent on theft or damage. And we're seeing the same thing happening now in the realm of privacy, where conflict has arisen between those who wish to use technologies such as encryption to keep their communications private, for whatever reason, and others who believe they must be able to intercept and collect these same messages and conversations. In the wake of recent terrorist attacks, the debate about whether individuals and organisations have the right to protect their communications with encryption has heated up. Law enforcement and intelligence agencies insist they cannot protect us without the ability to intercept any and all communications. But human rights advocates believe that privacy is a fundamental right. Steve Mansfield-Devine explores the issue and asks if we have enough information for a reasoned debate.